2017
DOI: 10.1007/s10517-017-3722-1
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory Bed, Microcirculation, and Smoking-Associated Endothelial Dysfunction in Young Adults

Abstract: Computer-assisted video biomicroscopy of bulbar conjunctiva was employed to examine the sequelae of endothelial dysfunction manifested by microcirculatory bed abnormalities and microcirculation disturbances. The signs of endothelial dysfunction provoked by tobacco smoking in young adults disappeared after cessation of smoking, which resulted in pronounced widening of arterioles and capillaries as well as moderation of intravascular erythrocyte aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Central obesity as well as smoking may induce relative increase in BP in SCD patients through direct effect on the kidneys and/or insulin resistance-induced activation of the sympathetic nervous system and renin angiotensin aldosterone system [14] [29] [30]. Microalbuminuria in SCD could be both a cause and a consequence of high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Central obesity as well as smoking may induce relative increase in BP in SCD patients through direct effect on the kidneys and/or insulin resistance-induced activation of the sympathetic nervous system and renin angiotensin aldosterone system [14] [29] [30]. Microalbuminuria in SCD could be both a cause and a consequence of high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the outflow of the aqueous humor through the trabeculectomy and filtering bleb requires a functional vessel network to be drained into the systemic circulation. Previous researchers indicated that tobacco smoking alters the microcirculation of the conjunctiva, causing endothelial dysfunction (28) as well as affecting the episcleral venous pressure increase due to vasoconstriction (13,14) . Another factor in the failure of these cases might be the restriction of the outflow of aqueous humor beyond the trabeculectomy site.…”
Section: Figurementioning
confidence: 99%
“…Finally, endothelial dysfunction - often defined as impaired NO bioavailability - acts as a common player in most cardiovascular (CV) risk factors ( Rajendran et al, 2013 ), underlining the importance of endothelial NO signaling in CV ageing and disease. Such risk factors include hypertension ( Panza et al, 1990 ; Perticone et al, 2001 ), arterial stiffness ( Leloup et al, 2019 ), smoking ( Korneeva and Sirotin, 2017 ), diabetes ( Calver et al, 1992 ), obesity ( Engin, 2017 ), inflammation ( Yang et al, 2016 ), and oxidative stress ( Cai and Harrison, 2000 ).…”
Section: Introductionmentioning
confidence: 99%